Design, synthesis, biological evaluation and cellular imaging of imidazo[4, 5-b]pyridine derivatives as potent and selective TAM inhibitors. Issue 20 (1st November 2018) - Baladi, Tom; Aziz, Jessy; Dufour, Florent; Abet, Valentina; Stoven, Véronique; Radvanyi, François; Poyer, Florent; Wu, Ting-Di; Guerquin-Kern, Jean-Luc; Bernard-Pierrot, Isabelle; Garrido, Sergio Marco; Piguel, Sandrine
Graphical abstract: Highlights: A series of novel imidazo[4, 5- b ]pyridines was prepared. Highly potent TAM inhibitors were identified. Two compounds demonstrated high activity and selectivity against AXL and MER. An unexpected nuclear localization of compound 10Bb was observed with NanoSIMS technology. Abstract: The TAM kinase family arises as a new effective and attractive therapeutic target for cancer therapy, autoimmune and viral diseases. A series of 2, 6-disubstituted imidazo[4, 5- b ]pyridines were designed, synthesized and identified as highly potent TAM inhibitors. Despite remarkable structural similarities within the TAM family, compounds 28 and 25 demonstrated high activity and selectivity in vitro against AXL and MER, with IC50 value of 0.77 nM and 9 nM respectively and a 120- to 900-fold selectivity. We also observed an unexpected nuclear localization for compound 10Bb, thanks to nanoSIMS technology, which could be correlated to the absence of cytotoxicity on three different cancer cell lines being sensitive to TAM inhibition.